Notes on the cultural life of the Democratic Republic of Vietnam - Weiss, Peter (Calder & Boyars, 1970)
By means of extensive historical information, Peter Weiss shows how totally the intellectual and cultural life of this nation is interwoven with its political and military struggle. Actual excerpts from Vietnamese stories, descriptions of their posters, slogans, festivals, plays written by workers, give a unique insight into the day-t-day cultural life of this war-torn nation.